Using a cooperative learning strategy to increase undergraduate students' engagement and performance: Bahir Dar university Psychology graduating students in focus - Andargachew Moges Agonafir (College of education, Bahir Dar University, 2023)
In the 21st century, preparing university students for real work and lifelong learning requires instructors to serve as facilitators of learning rather than as providers of information. Instruction needs to be learner-centered, active, enjoyable and engaging. As one form of active learning strategy, cooperative learning (e.g. group assignment) helps students to collaborate in the task actively and this in turn improves their learning engagement and performance. However, in my undergraduate course, when I encourage students to do assignments in groups, many of them do not take it seriously and are not committed, the final product being poor in terms of quality and participation. The objective of this action research was to improve the educational value of group assignment as one form of cooperative learning strategy by way of designing the task thoughtfully, following up and motivating students, providing constructive and timely feedback and ensuring greater engagement of students in the task. Third year psychology students volunteered to participate in the project. Phase I and Phase II (preliminary and actual action implementation make up the action research project). The outcomes of the preliminary and actual action implementation were then compared. The findings revealed that as a result of the intervention, students developed positive attitudes towards group assignment and they were more engaged in the second assignment as compared to the first (t= 6.51, p= 0.05). Students' performances in the second test and group project was also improved (t= 2.80, p=0.05 and t=7.67, p=0.05 respectively). Based on the findings, implications for further research and action are suggested